Trauma in Edgar Allan Poe’s “The Black Cat” - Muhammad Ismansyah Hidayat; Nia Nafisah (Passage, 2020)
This research aims to analyze trauma in short story "The Black Cat" (1843) by Edgar Allan Poe. Trauma in a way can be described as a recollecting memory of unpleasant events that may harm the mind of the one who suffers it. Studies on trauma in Poe's story are mentioned in Journal The Edgar Allan Poe Review (2019) as part of its further study on Poe's works. To fill the gaps in the research on "The Black Cat", this study aims to analyze the construction of trauma in the story and its effect on the story in narrative form. The data is analyzed using textual analysis trough close reading activity. The data then is interpreted using Caruth’s (1996) model on analyzing trauma in literature. The results show that (1) trauma is suffered through narrator’s attachment with the cat, (2) narrator’s regret of his wrongful violence, (3) through the repeating appearance of the cat, the trauma is reconstructed in the story, and (4) through trauma the character suffer mental deteriorations. The research concludes that trauma patterns based on Caruth's (1996) study appear in the story and it may help further study narrative in trauma study.Keywords: Trauma, Edgar Allan Poe, Cathy Caruth, The Black Cat, Narrative